Vestimenta drawing in use by the Romans : toward an archive of Pompeii clothing patterns - Avella, Alessandra (2022)
Abstract : This research treats about the women’s cloth-ing drawing used in classical Pompeii, aiming to integrate the results of scientific studies developed in other disciplines on clothing in ancient Rome and in the Provinces of its Empire with those of the Drawing dis-cipline. The research is based on the disci-plinary approach of Drawing in the study of iconographic sources, starting from the graphic analysis of the classical iconography of the National Archaeological Museum of Naples (MANN), compared with the histo-riographical sources for the representation of the main women’s tailoring patterns and both decorative and chromatic motifs, also in relation to the natural fibers of which the fabrics were made. The result of this analysis is an unpublished, systematic collection of technical drawings (patterns) of the various women’s clothing types, that bring back to the drawing a character of critical analysis rather than illustrative as often occurs in the scientific literature on the subject.